Annual Report on Exchange Arrangements and Exchange Restrictions 2007. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2007)
Only the IMF is officialy responsible for reporting the foreign exchange arrangements, exchange and trade restrictions, and prudential measures of its 185 member countries. This report draws upon information available to the IMF from a number of sources, including data provided in the course of official staff visits to member countries. Published since 1950, this authoritative, annually updated reference is based upon a unique IMF-maintained database that tracks monetary exchange arrangements for each of its 185 members, including historical information, along with entries for Hong Kong SAR (People's Republic of China) and Aruba and Netherlands Antilles (both Kingdom of the Netherlands). An introduction to the volume provides a summary of recent global trends and developments in the areas covered by the publication. It also provides insight into the types of capital controls most frequently used by countries dealing with increased capital inflows. Individual chapters for each member country report exchange measures in place, the structure and setting of exchange rates, arrangements for payments and receipts, procedures for resident and nonresident accounts, mechanisms for import and export payments and receipts, controls on capital transactions, and provisions specific to the financial sector. A separate section in each chapter lists changes made during 2006 and the first half of 2007. Information is presented in a clear, easy-to-read tabular format.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet